Global initiatives for waste reduction and cutting food loss - Gunjal, Aparna B., 1981-; Waghmode, Meghmala S.; Patil, Neha N.; Bhatt, Pankaj (Advances in environmental engineering and green technologies (AEEGT) book series., 2019)
"This book examines the methods of global initiatives for reducing waste reduction and cutting food loss. It also explores the idea of effective management of food waste"--